Optimizing Communication and Edukreatif Marketing Management of MelonMu Jama'ah Tani Gondosuli, Muntilan - Nunik Hariyanti; Rifky Dora Wijayati; Ifada Rahmayanti; Intan Rahma Deyaka (Warta LPM, 2025)
Jamaah Tani Muhammadiyah (JATAM) Gondosuli, a farmer located in the foothills of Mount Merapi, Indonesia, faces challenges in expanding market reach and professionalizing agricultural marketing. Despite fertile conditions and melons as a primary commodity, traditional marketing methods, limited organizational documentation, and low digital literacy constrain growth. This study aims to optimize JATAM’s communication and marketing strategies by integrating principles of Integrated Marketing Communication (IMC), enhancing English language proficiency, and leveraging digital platforms. A mixed-method approach was employed, including training interventions, pre- and post-assessments of marketing and management competencies,  as well as monitoring of digital engagement metrics. 30 participants from JATAM members involved in MelonMu Edukreatif activities, with data collected through structured assessments, interviews, and digital analytics. Results indicate significant improvements: post-training assessments showed increased knowledge and skills in marketing communication and institutional management, while digital engagement metrics demonstrated wider audience reach and higher brand visibilit. Integrating IMC principles enabled consistent messaging across traditional and digital channels, enhancing consumer trust and professional identity. English-language content facilitated access to broader national and international markets, supporting strategic partnerships and export opportunities. Thes study concludes that combining traditional and digital strategies, supported by capacity building and and systematic, monitoring, effectively strengthens local agricultural marketing. Recommendations include continued English and digital literacy training, expansion of digital marketing initiatives, and ongoing evaluation of Return on Investment (ROI) to ensure sustainable growth and economic resilience for farmer groups. These findings highlight the critical role of structured communication, language proficiency, and digital integration in enhancing community-based agricultural programs.